Características de latossolos roxos desenvolvidos de rochas alcalinas e básicas de Jaboticabal, SP - Centurion, J.F. [UNESP]; Andrioli, L. [UNESP]; Marques Jr., J. [UNESP]; Marchiori, D. G. (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 1995)
Comparou-se as características químicas, físicas e mineralógicas de Latossolos Roxos desenvolvidos de rocha alcalina (LRe) e de rocha eruptiva básica (LRd), da região de Jaboticabal, SP. Os resultados indicaram que o LRe apresenta-se num estádio de desenvolvimento, comparativamente, menos evoluído que o LRd, enquanto esse se apresenta com tendência para a maturidade. Os menores teores de argila e ferro total e maiores teores de saturação por bases, Ki e CTC da fração argila apresentados pelo LRe comprovam esta tendência. Conclui-se que a ocorrência de Latossolo Roxo eutrófico no campus da UNESP-Jaboticabal, pode estar associada a participação de rochas alcalinas na sua pedogênese.

A comparative study was carried out on chemical, physical and mineralogical characteristics of dusky red latosols originated from the weathering of alcaline (LRe) and basic eruptive rocks (LRd), of the Jaboticabal country Brazil The results showed that the LRe presented a younger development stage than LRd, while this soil showed a tendency to maturity. This trend was corraborated through the lower clay and total Fe2O3, contents and higher base saturation contents, Si2O/Al2O3 molecular ratio (Ki) and clay f ration CEC presented by LRe. It can be concluded that the occurrence of eutrophic dusky red latosols hi the UNESP-Jaboticabal campus may be due to the influence of alcaline rocks.
Characteristics of dusky red latosols developed from alcaline and basic rocks in Jaboticabal, SP
Keywords: latossolo roxo; rocha alcalina; pedogênese; dusky red latosol; alcaline rocks; pedogenesis